Pemikiran dan Gerakan Qurban Lintas Agama Tuan Guru Batak di Simalungun - Lubis, Muallim (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
The concept and movement of Interreligious Qurban, initiated by Tuan Guru Batak, a murshid of the Naqshbandiyah Khalidiyah order in Simalungun, North Sumatra, represent a social innovation aimed at fostering interreligious harmony. This movement is realized through the Qurban ritual during Eid al-Adha, involving various community elements, including religious leaders, Muslim and non-Muslim communities, and local government officials. The distribution of qurban meat is carried out indiscriminately, regardless of religious background, reflecting a strong spirit of solidarity and tolerance within the multicultural society, particularly in Nagori Jawa Tongah. This study aims to analyze the thoughts and implementation of the Interreligious Qurban Movement and its impact on social harmony. Employing a qualitative descriptive approach, the research collected data through in-depth interviews and document analysis from various local and national media sources. The findings reveal that this movement not only strengthens social relations but also serves as a model for religious diversity in Simalungun. The success of this initiative is evident in the establishment of the Interreligious Qurban Activity Center at the Sufi House and Civilization of Pondok Pesulukan Serambi Babussalam. These findings suggest that the qurban ritual can function not only as a religious obligation but also as a social instrument for fostering tolerance and social cohesion in a pluralistic society.